2016
DOI: 10.3846/20296991.2016.1226388
|View full text |Cite
|
Sign up to set email alerts
|

Using Pixel-Based and Object-Based Methods to Classify Urban Hyperspectral Features

Abstract: Object-based image analysis methods have been developed recently. They have since become a very active research topic in the remote sensing community. This is mainly because the researchers have begun to study the spatial structures within the data. In contrast, pixel-based methods only use the spectral content of data. To evaluate the applicability of object-based image analysis methods for land-cover information extraction from hyperspectral data, a comprehensive comparative analysis was performed. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…After analysis of the measured spectrum and JHU spectrum library, the TASI emissivity data in the study were divided into 27 types of lithological units (the corresponding sequence number). These are andesite (1), dolomite marble (2), marble (3), two-mica quartzite (4), monzonitic granite ( 5), monzodiorite (6), biotite plagioclase granulite (7), granite porphyry ( 8), granodiorite porphyry (9), granodiorite (10), limestone (11), diabase (12), pyroxenite (13), gabbro diorite (14), moyite (15), plauenite (16), sericite felsic slate (17), sub-rhyolite (18), diorite-porphyrite (19), diorite (20), serpentine (21), aposandstone (22), plagiogranite (23), basalt (24), dacite (25), mica slate (26), and felsic rock (27). The 50 samples were selected randomly for each type of lithology, of which 40 samples were used as training samples and 10 samples were used as test samples to carry out the lithological classification experiments in the study area.…”
Section: Training and Test Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…After analysis of the measured spectrum and JHU spectrum library, the TASI emissivity data in the study were divided into 27 types of lithological units (the corresponding sequence number). These are andesite (1), dolomite marble (2), marble (3), two-mica quartzite (4), monzonitic granite ( 5), monzodiorite (6), biotite plagioclase granulite (7), granite porphyry ( 8), granodiorite porphyry (9), granodiorite (10), limestone (11), diabase (12), pyroxenite (13), gabbro diorite (14), moyite (15), plauenite (16), sericite felsic slate (17), sub-rhyolite (18), diorite-porphyrite (19), diorite (20), serpentine (21), aposandstone (22), plagiogranite (23), basalt (24), dacite (25), mica slate (26), and felsic rock (27). The 50 samples were selected randomly for each type of lithology, of which 40 samples were used as training samples and 10 samples were used as test samples to carry out the lithological classification experiments in the study area.…”
Section: Training and Test Samplesmentioning
confidence: 99%
“…A relatively complete method system has been formed 22 29 A series of studies have shown that hyperspectral remote sensing data can distinguish the undistinguishable substances in multispectral remote sensing data due to its rich spectral information, which can help obtain accurate classification results. Zhang and Li 30 proposed the determining reference spectra method based on SAM for lithological mapping with EO-1 hyperion hyperspectral data.…”
Section: Introductionmentioning
confidence: 99%
“…The pixel-based classi cation method often results in "salt and pepper noise," which affects classi cation accuracy [19]. In contrast, the object-oriented(OO) classi cation method considers factors such as pixel context, object scale, and spatial consistency, effectively handling salt and pepper noise in images and improving classi cation robustness.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques are included in the software as standard as they have been used for the analysis of remote sensing data (SFF [73][74][75], SAM [76][77][78], BE [79][80][81]). For the analysis of heritage based hyperspectral data only SAM appears to have been used previously [42,82,83].…”
Section: Spectralonmentioning
confidence: 99%